Dusza, monstra i życie na Księżycu. Teoria antropologiczna w barokowej „scientia curiosa” Wojciecha Tylkowskiego - Raubo, Grzegorz (Wydawnictwo Naukowe UAM, 2013)
The article deals with the main points of the anthropological theory presented in the work of a baroque encyclopedist Wojciech Tylkowski which is entitled Uczone rozmowy [Learned Conversations] (1692). This theory combined the elements of theology, philosophy, science and common knowledge. It was presented as scientia curiosa, i.e. a convention which was used during the baroque era to popularize science. The most important aspects of the theory are: the concept of the human soul, four temperaments, the structure and operation of sense organs, the reasons for monstrous births, origins and manifestations of insanity, care of a guardian angel for a man, speculations about the idea of plurality of worlds and the possibility of people living on the Moon.
A soul, monsters and life on the Moon. Anthropological theory in Wojciech Tylkowski’s baroque scientia curiosa